Underlying and contributing causes of mortality from CDC WONDER—Insights for researchers - Abdul Mannan Khan Minhas; Laurence S. Sperling; Sadeer Al-Kindi; Dmitry Abramov (American Heart Journal Plus)
Background: The multiple cause of death files available through the Center for Disease Control and Prevention Wide-ranging Online Data for Epidemiologic Research (CDC WONDER) present underlying and contributing causes of mortality. We sought to evaluate potential differences in mortality reporting that may occur based on utilization of only underlying versus utilization of both underlying and contributing cause of mortality. Methods: All-cause and top 5 underlying causes of deaths in individuals ≥25 years of age from 2011 to 2019 occurring within United States were extracted from CDC WONDER. Deaths for the top 5 underlying causes of death as underlying and as underlying or contributing causes were extracted. For each cause, we calculated the percentage of the deaths that would be reported if only the underlying versus the underlying or contributing mortality was reported. Results: Between 2011 and 2019, the top 5 underlying causes of mortality were heart disease, malignant neoplasm, chronic lower respiratory disease, cerebrovascular disease, and accidents. For these causes, the percentages of deaths presented by reporting (underlying)/(underlying or contributing) causes were 53 %, 91 %, 50 %, 59 %, and 79 % respectively. Discussion/conclusion: Data within the commonly utilized multiple cause of death files from CDC WONDER demonstrate that reliance solely on the underlying cause of mortality may underestimate important contributions of common contributing causes. These findings could aid in the understanding of published research and may shape the framework for future studies utilizing multiple cause of death data through CDC WONDER.